DEVELOPMENT AND EXPERT VALIDATION OF A PROBLEM-BASED LEARNING ACCOUNTING E-MODULE INTEGRATED WITH GAMIFICATION - Herdiana Br Sitompul; Saidun Hutasuhut; Muhammad Bukhori Dalimunthe (RADJA PUBLIKA, 2026)
This study aims to develop a gamification-integrated Problem Based Learning (PBL) e-module based on Moodle and to examine its feasibility as instructional material for eleventh-grade accounting students at vocational high school. The study was motivated by the low level of students’ critical thinking skills and learning outcomes, particularly in recording trading company transactions, which are still dominated by conventional teaching approaches. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. The research subjects were eleventh-grade accounting students at SMK Negeri 1 Patumbak in the 2025/2026 academic year. Data were collected through expert validation involving material experts, media experts, and instructional design experts, as well as product trials including individual testing, small group testing, and large group testing. The results indicate that the gamification-integrated PBL e-module is feasible for use in accounting learning. Material expert validation obtained an average score of 3.9 (78%) categorized as valid, media expert validation obtained a score of 4.15 (83%) categorized as very valid, and instructional design expert validation obtained a score of 4.11 (82%) categorized as very valid. The individual trial resulted in a feasibility percentage of 80% (valid), the small group trial achieved 83% (very valid), and the large group trial reached 93% (very valid). Overall, the e-module achieved an average feasibility score of 83%, categorized as very valid. These findings indicate that the developed e-module meets feasibility criteria in terms of content, media, and instructional design, and has strong potential to support interactive, contextual, and student-centered accounting learning. Keywords: e-module, problem based learning, gamification, Moodle, vocational accounting education